Language Shift and Youth Slang in Digital Communication: Evidence from Social Media Discourse - Tarma Tarma; Bunga Dwi Fani Ritonga (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates language shift and youth slang within digital communication, examining how adolescents and young adults (aged 15–24) utilize social media platforms Instagram, TikTok, and Twitter to produce, disseminate, and negotiate semiotic meaning. Employing an empirical mixed-methods design, data were collected through naturalistic observation of 2,500 social media posts, content scraping of slang expressions, and 40 semi-structured online interviews, enabling triangulation of textual, visual, and conversational semiotic elements. Quantitative analysis revealed differential frequency and platform-specific distribution of slang categories, while qualitative findings highlighted multifunctional deployment of humor, intimacy, rebellion, and topical innovation as core semiotic roles. Influential factors driving adoption included peer endorsement, platform affordances, algorithmic exposure, cognitive engagement, and socio-cultural context, with temporal dynamics and network centrality accelerating lexical innovation. Findings underscore that language shift in digital environments is an emergent, socially regulated, and contextually mediated process, reflecting both identity negotiation and cultural adaptation. This research contributes a robust framework for understanding digital language evolution, offering insights into youth sociolinguistics, semiotic function, and the interplay of social, technological, and cognitive determinants in contemporary communication.